Perancangan Sistem Informasi Akuntansi Persediaan Barang Dagang Menggunakan SAK EMKM Berbasis Web - Hery Dwi Yulianto; Dyan Fachri Maulana (Labkat Press KA FTIK UNIKOM, 2020)
The purpose of this study is to make a design of accounting information systems for merchandise inventory at the Cireng Cinta Shop with a website-based and SAK EMKM, where it is expected that the development of the system can provide an overview of the proper application of the merchandise inventory accounting information system. Currently Cireng Cinta Shop still uses manual processing throughout, where when ordering products the product must come to the seller's place to place an order or via SMS or WA, after that when the collection is not given proof of payment that should be evidence for later reporting. Inventory management is still manually which is not taken into account. Therefore, with the design of an accounting information system for merchandise inventory to facilitate application development in accordance with SAK EMKM and activities. The method used in this research is descriptive method and also survey, where by conducting a direct survey at the site of the activity makes it easy to see firsthand the shortcomings and potential that might be developed further. The unit of analysis examined in this study is the Cireng Cinta Shop, the population studied is the inventory report from January-April 2020. The results of this study are expected to be able to find out about merchandise inventory information systems, as well as design systems that will be applied to companies. The design process of making ERD, context diagrams, program menu structures, account codes, general journals, and merchandise inventory cards are required by the company. With the development of this system, it will facilitate the process of integrating company problems with future application design.